(untitled) (Irrigation and Melioration, 2026)
This article presents a methodology for evaluating and calibrating the metrological characteristics of the “Smart Channel” device designed for measuring water discharge in open channels under laboratory conditions. An 80×80 cm device sample was selected as the research object. The experiments were conducted in the “Hydraulics and Hydrometry” laboratory of “Smart Solutions System” LLC, located in the Kuyichirchik district of Tashkent region. The device operates based on the velocity–area method, in which water discharge is determined using the average flow velocity and wetted cross-sectional area. Flow velocity is recorded layer by layer using a total of 32 ultrasonic sensors arranged in 8 rows, and the overall average velocity is then calculated. During the study, the maximum water conveyance capacity of the device and its errors compared with an electromagnetic reference flowmeter and the volumetric method were determined. In the initial tests, the maximum discharge was 799.23 l/s, while the errors ranged from 5.98% to 14.30%. This indicated the need to improve the initial calculation algorithm of the device under high-flow conditions. Therefore, a calibration coefficient was developed based on the results obtained from the reference flowmeter and the volumetric method and was integrated into the device software. After calibration, the maximum discharge increased to 890.57 l/s, while the errors decreased to the range from 2.47% to +2.37%. The results showed that verification and calibration significantly improved the accuracy of the device, provided a scientific and practical basis for reliable digital measurement of water discharge in open channels, and supported the effective implementation of the device in practice.